Occurrence of helminths in sheep - Abdullah Sani, Rehana; Awang Iskandarzulkarnian, Pengiran Rayari; Sheikh Omar, Abdul Rahman; Ungku Mohsin, Ungku Chulan (Persatuan Doktor Veterinar Malaysia, 1986)
Helminths found in the gastrointestinal tracts of 32 out of 42 sheep were mainly Hemonchus contortus (90%), Trichostrongylus colubriformis (59%), Oesophagostomum columbianum (25%) and Moniezia expansa (22%). There was an inverse relationship between age and worm counts for Oesophagostomum sp. and Trichuris sp. The postmortem lesions of anaemia and oedema were consistently observed in the presence of 'varying numbers ofH. contortus